Enablers of and barriers to ART adherence among female sex workers in mid-western Uganda: a qualitative study - David Friday Apuulison; Brenda Nabawanuka; Michael Muhoozi; Julian Aryampa; Pauline Irumba; Edson Katsomyo; Moses Asiimwe; Joshua Epuitai; Pardon Akugizibwe; Wasswa George; John Rubaihayo (AIDS Research and Therapy)
Abstract Introduction Female sex workers (FSWs) in Uganda experience numerous barriers to antiretroviral therapy (ART) adherence. We used the planned behavior theory to help explore the enablers and barriers to ART adherence among FSWs. Understanding the barriers to ART adherence may help contribute to the development of interventions to improve ART adherence among the FSWs. Materials and methods A descriptive qualitative study was conducted in Fort portal City. We conducted 30 in-depth interviews among FSWs who had been taking ART for at least six months. Furthermore, six key informant interviews were conducted with healthcare workers and leaders of the FSWs initiative. Data collection lasted for two months. Thematic deductive analysis was applied to analyse the data through the lens of the theory of planned behavior. Findings The attitudes, subjective norms, and perceived behavioral control influenced adherence to ART. Positive attitudes including perceived benefits of ART, and experiencing positive outcomes from taking ART were seen to enable its adherence. Subjective norms such as social support, disclosure of HIV status, seeing others take ART, and aspirations of longer life enabled ART adherence. Taking ART in the morning, responsive and respectful healthcare workers, and availability of food/basic needs facilitated compliance with ART adherence. Negative attitudes such as misconceptions and fear of side effects hindered ART adherence. Social disapproval of sex work and or HIV, lack of social support, gender-based violence, non-disclosure, stigma, and abandonment hindered the use of ART among FSWs. Socio-economic constraints (e.g., food scarcity), and occupation-related factors (substance use, incarceration, busy and predictable schedules, and abrupt migrations) were the additional barriers to ART adherence. Conclusion ART adherence among FSWs was influenced by attitudes, subjective norms, and perceived behavioral control. Addressing these barriers in ART adherence through targeted interventions could facilitate ART adherence and improve health outcomes among FSWs.